Estimates of the gene frequency of BRCA1 and its contribution to breast and ovarian cancer incidence. - Ford, D (1995)
The majority of multiple-case families that segregate both breast and ovarian cancer in a dominant fashion are due to mutations in the BRCA1 gene on chromosome 17q. In this paper, we have combined penetrance estimates for BRCA1 with the results of two population-based genetic epidemiological studies to estimate the gene frequency of BRCA1. On the assumption that the excess risk of ovarian cancer in first degree relatives of breast cancer patients and the breast cancer excess in relatives of ovarian cancer patients are both entirely accounted for by BRCA1, we estimate that the BRCA1 gene frequency is 0.0006 (95% confidence interval [O.002-0.002]) and that the proportion of breast cancer cases in the general population due to BRCA1 is 5.3% below age 40 years, 2.2% between ages 40 and 49 years, and 1.1% between ages 50 and 70 years. The corresponding estimates for ovarian cancer are 5.7%, 4.6%, and 2.1%, respectively. Our results suggest that the majority of breast cancer families with less than four cases and no ovarian cancer are not due to rare highly penetrant genes such as BRCA1 but are more likely to be due either to chance or to more common genes of lower penetrance.